The popular teacher problem in M. Grinchenko’s intellectual heritage (Pedagogy of Higher and Secondary Education, 2013)
Lashko M. V. The popular teacher problem in M. Grinchenko’s intellectual heritageThe article characterizes M. Grinchenko’s little known works and her ideas about popular teacher, distinguishes some questions which interested her, and analyses her demands to teachers personal characteristics.
Keywords: popular teacher; school; pupils; intellectual heritage; Maria Grinchenko